(untitled) (Journal of Hama University, 2022)
Introduction: The Retention of the denture is of utmost interest to the retention of the maxillary denture during functional movements. It must maintain contact with the anterior portion of the soft palate, so the available literature states that addition of posterior palatal seal markedly increases the retention of the denture. Aim of the Study: The aim of this study is to evaluate the effect of using light-cured acrylic to create the posterior palatal seal in maxillary removable complete dentures. Materials and Methods: The sample included 12 maxillary edentulous patients, ranging in age between 55-71 years. Two maxillary definitive impressions were made by using zinc oxide- Eugenol. Posterior palatal seal area on the impressions was determined and transfer the marked zone. First definitive impression was dried to create the form for the pps using light-cured acrylic then to customize light-cured acrylic, the impression was placed into the mouth. Second definitive cast was carved according to marked zone where vary from zero at the anterior line to the depth of 1 to 1.5 mm along the posterior border .The posterior and total retention of the upper denture is Measured for each patient, by using spring. The data obtained was statistically analyzed using Student’s independent T-test. The level of confidence was set at 95%. Results: The result showed that there were statistically significant differences in the mean the posterior retention between the group in which Light-Cured Acrylic was used and the group of traditional Technique and in total retention (P=0.05). Conclusions: The posterior palatal seal adaptation used by Light-Cured Acrylic is greater in retention than the scrap technique, without effect of gender on the total retention in the two techniques